Syntactic Echoes Of Pronominal Cliticization And Grammaticalization: The Case Of Old High German First‐Person Plural ‐Mes. (23rd January 2018) - Somers, Katerina; Allison, Mary; Boutilier, Matthew; Howell, Robert
Abstract: The origin of first person plural (1PL) 'long' forms of the type faramês/‐mes '(we) go' in Old High German (OHG) is one of the most intractable problems in the history of the Germanic languages. Because these forms are confined only to OHG and have no obvious parallel elsewhere in Germanic or Indo‐European, most of the tools of the comparative method are of little use, with the result that the many accounts put forward over the past two centuries rely on a series of unlikely and ad hoc assumptions. What is more, previous work has focused on the one aspect of the problem that scholars are least likely to solve given the array of texts we presently have at our disposal, while paying little attention to what we argue is the more promising line of inquiry. That is, existing studies discuss in detail the possible morphological sources of ‐mes and their phonological development and focus little on the syntactic environments in which verbs inflected with ‐mes occur. We intend to reverse this trend through a comprehensive examination of ‐mes across the OHG corpus, with a particular focus on two of its major monuments, the OHG Tatian and Otfrid's Evangelienbuch ; this analysis shows that the syntactic distribution of ‐mes ‐inflected verbs point to the suffix being diachronically and synchronically pronominal. Thus, we conclude that ‐mes must have arisen as the result of pronominal cliticization, a suggestion first put forth by Kuhn (1869 ) and Paul (1877 ).